2023
DOI: 10.1007/s40808-023-01705-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of uncertainties in a complex modeling chain for predicting reservoir sedimentation under changing climate

Abstract: Long-term predictions of reservoir sedimentation require an objective consideration of the preceding catchment processes. In this study, we apply a complex modeling chain to predict sedimentation processes in the Banja reservoir (Albania). The modeling chain consists of the water balance model WaSiM, the soil erosion and sediment transport model combination RUSLE-SEDD, and the 3d hydro-morphodynamic reservoir model SSIIM2 to accurately represent all relevant physical processes. Furthermore, an ensemble of clim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…This is obtained using the acoustic backscatter signal from two side-looking H-ADCPs (Horizontal acoustic Doppler Current Profiler; 0.6 and 1.2 MHz). Nevertheless, these measurements are only available for water depths at the gauging station exceeding 1 m (Pesci et al, 2023). In addition, using the pebble count method in the focused area of this study, the substrate grain size distribution curve was measured in the field, describing the bed material by D 50 of 19 mm, the mean particle size of 25 mm, and the standard deviation of 1.49.…”
Section: Measured Datamentioning
confidence: 99%
“…This is obtained using the acoustic backscatter signal from two side-looking H-ADCPs (Horizontal acoustic Doppler Current Profiler; 0.6 and 1.2 MHz). Nevertheless, these measurements are only available for water depths at the gauging station exceeding 1 m (Pesci et al, 2023). In addition, using the pebble count method in the focused area of this study, the substrate grain size distribution curve was measured in the field, describing the bed material by D 50 of 19 mm, the mean particle size of 25 mm, and the standard deviation of 1.49.…”
Section: Measured Datamentioning
confidence: 99%
“…In this case, the annual glacier outputs generated from OGGM allow to perform model simulations starting at any desired year, hence overcoming dependence on observed outlines. Furthermore, the successful application of both models in water-scarce regions (examples of studies carried out with WaSiM can be found in Cornelissen et al, 2013;Idrissou et al, 2020;Pesci et al, 2023 andwith OGGM, in Dixit et al, 2021;Ross et al, 2023) encourages the use of the coupling scheme in such areas. As a changing climate may significantly impact water availability by the end of the century, the prediction of the catchment's hydrological response becomes crucial.…”
Section: Applicability Of the Coupling Scheme In Other Catchmentsmentioning
confidence: 99%